Evolution of Abscisic Acid Signaling for Stress Responses to Toxic Metals and Metalloids - Hu, Beibei; Deng, Fenglin; Chen, Guang; Chen, Xuan; Gao, Wei; Long, Lu; Xia, Jixing; Chen, Zhong-Hua (Frontiers in Plant Science, 2020)
Toxic heavy metals and metalloids in the agricultural ecosystems are some of the crucial factors limiting global crop productivity and food safety. Industrial toxic heavy metals and metalloids such as cadmium, lead, arsenic have contaminated large areas of arable land in the world and their accumulation in the edible parts of crop is causing serious health risks to humans and animals. Plants have co-evolved with various concentrations of these toxic metals and metalloids in the soils and water. Some green plant species have significant innovation in key genes for the adaptation of abiotic stress tolerance pathways that are common for the tolerance to heavy metals and metalloids. Increasing evidences have demonstrated that phytohormone abscisic acid (ABA) plays vital roles in the alleviation of heavy metal and metalloid stresses in plants. Here, we trace the evolutionary origins of the key gene families connecting ABA signaling with tolerance to heavy metals and metalloids in green plants. We also summarize the molecular and physiological aspects of ABA in the uptake, root-to-shoot translocation, chelation, sequestration, reutilization and accumulation of key heavy metals and metalloids in plants. The molecular evolution and interaction between ABA signaling pathway and mechanisms for heavy metal and metalloid tolerance are highlighted in this review. Therefore, we propose that it is promising to manipulate ABA signaling in plant tissues to reduce the uptake and accumulation of toxic heavy metals and metalloids in crops through the application of ABA-producing bacteria or ABA analogues. This may lead to improvement of tolerance of major crops to heavy metals and metalloids.